2021
DOI: 10.2147/ndt.s331874
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Impact of Susceptibility-Weighted Imaging Prominent Veins in Acute Ischemic Stroke: A Systematic Review and Meta-Analysis

Abstract: Purpose:We aimed to determine the prognostic impact of prominent veins (PVS) after an acute ischemic stroke identified on susceptibility-weighted imaging (PVS-SWI). Methods: We searched for studies published in PubMed, Embase, Cochrane Library and Chinese Biomedical Literature Database. Poor functional prognosis, early neurological deterioration, and hemorrhagic transformation were evaluated. Risk ratios (RR) were pooled implementing a random effect model. We performed a subgroup analysis by treatment, locatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Regarding PVS-SWI, the latest quantitative meta-analysis included 16 cohort studies involving a total of 1605 patients, of which 11 studies concluded that the presence of PVS-SWI was related to poor prognosis in AIS, and 5 studies suggested no significant association. The meta-analysis showed that PVS-SWI was related to a poor 90-day functional prognosis and was more likely to show early neurological deterioration [ 10 ]. Unfortunately, this meta-analysis did not explore the correlation between PVS-SWI and malignant cerebral edema events, probably due to the lack of previous relevant studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding PVS-SWI, the latest quantitative meta-analysis included 16 cohort studies involving a total of 1605 patients, of which 11 studies concluded that the presence of PVS-SWI was related to poor prognosis in AIS, and 5 studies suggested no significant association. The meta-analysis showed that PVS-SWI was related to a poor 90-day functional prognosis and was more likely to show early neurological deterioration [ 10 ]. Unfortunately, this meta-analysis did not explore the correlation between PVS-SWI and malignant cerebral edema events, probably due to the lack of previous relevant studies.…”
Section: Discussionmentioning
confidence: 99%
“…PVS-SWI is related to the amount of deoxyhemoglobin in venous blood [ 8 ] and venous dilatation [ 9 ], indirectly reflecting the increased oxygen extraction fraction and hypoperfusion state. In previous studies, PVS-SWI was correlated with short-term functional outcomes, but its relationship with MCE outcome has not been systematically investigated [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, 20 studies reported the relationship between PVS and the prognosis of patients with AIS, 15 of which believed that PVS had a worse prognosis than those without PVS ( 8 – 22 ), while the other 5 suggested that the presence of PVS was not related to prognosis ( 23 – 27 ). A previous meta-analysis has indicated that PVS was related to a poor functional prognosis in patients with AIS ( 28 ). However, it remains inconclusive whether PVS has an independent effect on prognosis in terms of pathophysiological factors such as large vessel occlusion.…”
Section: Introductionmentioning
confidence: 99%